Інформаційний аспект українсько-румунського транскордонного співробітництва - Королевська, А. В.; Korolevska, A. V. (Східноєвропейський національний університет імені Лесі Українки, 2013)
The level of information report of cross-border cooperation between Ukraine and Romania on the basis of content analysis and content-monitoring is researched.
Informational aspects of Ukrainian-Romanian transboundary cooperation
А.В. Королевська, к. політ. н., доц. Хмельницького національного університету (Україна, м. Хмельницький)
Keywords: transboundary cooperation; Ukraine; Romania; informational aspect; content-analysis; content-monitoring